Optique adaptative et telescopes geants - Fusco, Thierry (Comptes Rendus. Mécanique, 2023)
Adaptive optics (AO), now installed on all the astronomical ground-based telescopes, make it possible to overcome the angular resolution limitations imposed by atmospheric turbulence. This article presents the state-of-the-art in the field of astronomical applications, and shows how adaptive optics has revolutionized ground-based astronomical observation over the last twenty years, overcoming countless scientific and technical challenges. Finally, we present how the concept will be applied, by 2030, on future giant telescopes to answer some of astronomy’s most fundamental questions concerning the birth of the universe or the existence of life outside the solar system.